Reconceptualizing temporality in and through multimedia storytelling: Making time with through thick and thin. Issue 2 (4th May 2018) - Lind, Emily R.M.; Kotow, Crystal; Rice, Carla; Rinaldi, Jen; LaMarre, Andrea; Friedman, May; Tidgwell, Tracy
ABSTRACT: What lessons about linearity are illuminated by the stories that engage our experience of queer fat bodies? The authors examine stories generated in the collaborative, community-based research project Through Thick and Thin . They analyze a selection of 3- to 7-minute microdocumentaries produced in the project that feature assemblages of queer sexuality, gender expression and identity, and other privileged or minoritized identifications (race, disability, class, indigeneity) in confrontation with weight-based stigma, expectations around eating and exercise, and experiences of pathologization. The athors argue that linearity requires a constant labor of improvement that seeks to restore and recover fat queer bodies to imagined state(s) of normalcy/health. By using concepts of queer and crip time, the authors illustrate how queer subjectivity—queered in terms of not only sexuality, but also body shape and size, and/or eating dis/order practice—finds itself out of sync with time: that is, how the project's storytellers are refused or engage in acts of refusing available futurities and instead construct and live subversive temporalities. In the authors' range of examples, they show and value how Through Thick and Thin storytellers, and by extension persons with queer and non-normative embodiments, live and move through and in effect, re- make time.